(untitled) (Docentes 2.0 Journal, 2025)
Information and Communication Technologies (ICT) have significantly transformed society, including education. Therefore, teachers must integrate a set of Digital Educational Resources (RED) into their pedagogical practices. The objective of the research was to analyze the use of RED in academic activities and the perception of teachers about these resources. A methodology was used under the pragmatic paradigm, inductive-deductive method, and mixed approach, with a sequential exploration design of a concurrent triangulation and cross-sectional type. It was carried out in December 2023. The sample was non-probabilistic, intentionally made up of 24 professionals, 12 teachers, and 12 directors of the same number of primary education centers in rural areas with access to the Internet and technological resources. The results indicated a low frequency in the planning and use of RED, which shows significant barriers, such as the need for more infrastructure and teacher training. Effective implementation of REDs can democratize and personalize learning by promoting student autonomy and empowerment. However, significant challenges were identified, such as the digital divide and the need for greater institutional support. This study underlines the importance of investing in infrastructure and ongoing training to overcome technological barriers and improve the perception and use of REDs in rural primary education. The findings are consistent with similar studies and highlight the urgency of a balanced strategic approach to transform education into the digital age.